Konfigurasi Ekspresi Keagamaan Artis Di Media Sosial - Bayu Mujrimin; Nurul Istiani; Muhammad Aziz (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
The religious expressions of the artist in the social media space have the potential to give an ambiguous impression to the public in responding to them. On the one hand, artists as religious people have the right to carry out their religious teachings in the public sphere. But on the other hand, the artist is also a public figure whose popularity is widely used by the industrial world. This study intends to identify the meaning of various religious expressions of some Indonesian artists in various accounts or social media channels. Through a phenomenological approach, the dramaturgical theory that was initiated by Erving Goffman is used as an analytical theory. This research data collection using observation and documentation techniques. Meanwhile, the data analysis technique is through data reduction, data presentation, and drawing conclusions. The results of the study conclude that religious expressions by some Indonesian artists in the social media space can be explained through three patterns. First, religious expression as religiosity. This pattern can be seen from the backstage which is shown as a religious person who carries out his religious teachings. Second, religious expression as a commodification of religion. This pattern can be seen from the appearance of the artists as brand ambassadors for certain business products. Third, religious expression as media capitalization. This pattern can be seen from the artist's religious expression following the media arrangement that emphasizes the elements of business and profit. The theoretical implication of this research shows that understanding and expression of religion can experience developments and changes in form in the dynamics of the construction of socio-cultural life.